Pseudomonas spp. Enriched in Endophytic Community of Healthy Cotton Plants Inhibit Cotton Verticillium Wilt - Zeng, Qingchao; Man, Xiaowu; Dai, Yucheng; Liu, Haiyang (Frontiers in Microbiology, 2022)
The plant microbiome plays a fundamental role in plant growth and health. However, detailed information regarding the plant endophytic microbiome during the infection period of a pathogen is largely unknown. Here, we investigated the microbial community of healthy and diseased cotton plants and the root exudate profiles of susceptible and resistant cultivars utilizing high-throughput sequencing and metabolomics. The results showed that the pathogen infection reduced bacterial diversity and significantly affected the bacterial community composition. The microbiome assembly is shaped predominantly by cultivars. The endophytic microbiome of the infected plants showed greater complexity than the healthy plants in network analysis. The results displayed that a total of 76 compounds were significantly different in the two groups, with 18 compounds showing a higher relative abundance in the resistant cultivars and 58 compounds in the susceptible cultivars. Pathway enrichment analysis showed that pathways related to plant hormone signal transduction, biosynthesis of various secondary metabolites, and biosynthesis and metabolism of amino acids were prominently altered. We also demonstrate that plants inoculated with Pseudomonas sp. strains showed increased resistance to the cotton Verticillium wilt compared with the control plants in pot experiments. Overall, it showed that the pathogen infection affected the community composition, and healthy plants displayed an enriched beneficial microbiome to combat the plant disease. These findings significantly advance our understanding of the endophytic microbiome assembly under the pathogen infection and develop microbiome-based solutions for sustainable crop production systems.